Who is that and what do they do? Showing connections between external services and your institutional repository - Draper, Daniel, author; White, Suzi, author (Colorado State University. Libraries, 2015)
Since the implementation of DigiTool for the Digital Collections of Colorado in 2007, the landscape of services available to academic institutional repositories has changed significantly. A recent migration to DSpace precipitated an assessment of the increased number of services available to support open scholarly information sharing. What's the difference between VIVO and Altmetric? How are Figshare and Globus services similar? This poster defines core functionality of many of these services and how they relate to DSpace. It also categorizes them into four key areas: alternative research metrics, data storage and delivery, faculty and institutional reporting, and digital preservation. The overview will help academic library staff assess the service solutions that can best complement their institutional repository's strategic goals. Presented at the 2015 DLF Forum on October 26, 2015.
Keywords: research metrics; digital preservation; data storage and delivery; data management systems